2017
DOI: 10.1128/jcm.00520-17
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Based Methods and Molecular Tools for Azole-Resistant Aspergillus fumigatus Detection in a Belgian University Hospital

Abstract: Azole-resistant Aspergillus fumigatus is an increasing worldwide problem with major clinical implications. Surveillance is warranted to guide clinicians to provide optimal treatment to patients. To investigate azole resistance in clinical Aspergillus isolates in our institution, a Belgian university hospital, we conducted a laboratory-based surveillance between June 2015 and October 2016. Two different approaches were used: a prospective culture-based surveillance using VIPcheck on unselected A. fumigatus (n ϭ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…We report the presence of TR 46 /Y121F/T289A now also from Iran, where until now only TR 34 /L98H had been isolated . This mutation, conferring voriconazole resistance, has been reported from both environmental (China, Taiwan, United Kingdom, Colombia, France, Germany, India, the Netherlands and Tanzania) and clinical sources (Spain, United Kingdom, France, Portugal, Argentina, Taiwan, Germany, China, Japan, United States, Denmark, Belgium and the Netherlands) (Table 1). All previous studies conducted in Iran for monitoring the mechanism of resistance among azole‐resistant A fumigatus in both clinical and environmental samples showed that the TR 34 /L98H mutation was reported with increasing frequency from 3.3% in 2013 to 6.6% in 2016 .…”
Section: Discussionmentioning
confidence: 73%
“…(12,21,22) Simultaneous detection of IA and identification of resistance mutations sparks an increasing interest in clinical settings for an earlier adaptation of antifungal therapy; of note A. fumigatus resistant strains have been related to a higher mortality rate, due to a delayed initiation of adequate treatment (23) . In this context, commercial kits targeting both A. fumigatus and cyp51A genes have been recently marketed, but their evaluation on clinical samples IA population is still scarce (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite all this work, only three commercial kits are currently available (AsperGenius, PathoNostics, Maastricht, Netherlands, MycoGENIE, Ademtech, Pessac, France and Fungiplex ® Aspergillus Azole-R IVD PCR, Bruker Daltonik GmbH, Bremen, Germany), attesting to the difficulty of developing robust molecular assays [113]. All three commercial real-time PCRs (RT-PCR) are designed to identify the promoter region insertion polymorphisms TR34/L98H and TR46/Y121F/T289A and specific alleles [109,[114][115][116][117][118][119]. Approaches targeting polymorphisms in the cyp51A open reading frame (ORF, e.g., G54, M220, G138, G448) [120][121][122] have lagged behind.…”
Section: Molecular Techniques For Discerning Cyp51a Resistance Polymomentioning
confidence: 99%